Audit of screening programme for congenital hypothyroidism in Scotland 1979–93. Issue 5 (1st May 1997) - Ray, M; Muir, T M; Murray, G D; Kennedy, R; Girdwood, R W A; Donaldson, M D C
Abstract : OBJECTIVE: To evaluate the efficiency of the screening programme for congenital hypothyroidism in Scotland and to determine the outcome in the cohort of children with positive testing for thyroid stimulating hormone (TSH). DESIGN: Establishment of comprehensive database for all Scottish infants with high TSH, detected on Guthrie screening. SUBJECTS: 344 infants born between August 1979 and December 1993 with TSH greater than 40 mU/l on initial Guthrie, or 15–40 mU/l on repeat Guthrie. MAIN OUTCOME MEASURES: Ages at time of: (a) Guthrie collection, (b) notification of positive result by laboratory, and (c) start of treatment; audit of late diagnosis/missed cases; categorisation of positive cases into definite and probable congenital hypothyroidism, transient TSH elevation, and uncertain status; educational status of children with definite and probable congenital hypothyroidism. RESULTS: 344 positive cases were categorised as having definite (224) and probable (11) congenital hypothyroidism, transient TSH elevation (88), and status uncertain (21). The overall incidence of definite/probable congenital hypothyroidism was 1 in 4400 live births. For the definite/probable groups median age of Guthrie collection was consistently between 6 and 7 days from 1983 onwards but for the whole cohort was later than 10 days in 10.5%. Median age of notification fell from 14 days in 1980 to 11 days in 1993. Median age of starting treatment ranged between 11 and 15 days from 1983 onwards. Treatment was delayed in four cases, three due to failed or late Guthrie card submission. Of 149 children with definite/probable congenital hypothyroidism who were of school age, educational status was ascertained in 139 (93%). Only two children (1.4%) were attending special school, one of whom was known to have mild hypothyroidism. Sixteen children (11.5%) were receiving extra help in mainstream education compared with 18% of control children in the Scottish very low birth weight study. CONCLUSION: The current screening programme is working well, but efficiency could be increased by earlier and more reliable Guthrie collection. A substantial proportion of children picked up on the screening programme have a transient rise in TSH rather than true congenital hypothyroidism. The incidence of special education and learning support in Scottish children with congenital hypothyroidism appears to be no different to that of the general population.